Às palavras, cidadãos: o debate competitivo como instrumento de ensino para cidadania - Caxilé, Priscila Soares (2023)
The present thesis believes that it is necessary to develop the construction of argumentation, through the teaching of oral genres, for high school students, aiming at the development of citizenship education. From this, our main objective is to analyze the construction of arguments by high school students, through the Competitive Debate, aspiring the development of citizen literacy. For that, we developed a didactic sequence, based on the model proposed by Schneuwly, Dolz and Noverraz (2004), to make the teaching of the argumentative oral genre Competitive Debate more didactic. In addition, we aim to show that the systematic teaching of this genre, based on a didactic sequence in the light of citizen literacy and the New Rhetoric by Perelman and Tyteca (2014), contributes to the development of argumentation and citizen literacy, a concept formulated by us based on Cosson (2015). We also seek to: a) elaborate, in the light of citizen literacy and the New Rhetoric, a didactic sequence for the work of the Competitive Debate textual genre in the High School classroom; b) describe the textual and paralinguistic aspects of the Competitive Debate genre; and c) analyze the rhetorical movements and argumentative strategies used by students in the production of this genre. Methodologically, we followed the following steps: formulation and application of the didactic sequence, application of a test to verify argumentative practices in which students had already participated; description of the textual and paralinguistic aspects of the competitive debates carried out during the didactic sequence and analysis of the types of arguments presented during the competitive debates produced by the students. In summary, as final considerations, we observed that there was a significant change in the organization and development of the argumentation throughout the didactic sequence, after analyzing the two productions of the oral genre Competitive Debate. They were carried out at the beginning and at the end of the proposed didactic sequence, presented through modules, in which we were able to propose didactic strategies that contributed to the development of the linguistic aspects present in the oral genre, such as the use of conversational markers, up to the structuring of the oral genre Competitive debate. In this way, we conclude that the argumentative competence and the production of an oral genre can be improved in a systematic way, and that the teaching of the argumentative competence, through the oral genre Competitive Debate, is a strong teaching instrument that contributes, significantly, to the development of literacy/citizen education in the classroom.